IMPLEMENTATION OF SYSTEM USABILITY SCALE IN THE DOCTOR APPOINTMENT APPLICATION DEVELOPMENT USING THE SCRUM METHOD - Chandra, Felly; Zul, Muhammad Ihsan (Politeknik Caltex Riau, 2024)
Healthcare facilities often face long queues and extended waiting times, disrupting the service process and increasing the risk of spreading infectious diseases. To address these challenges, this study utilized Scrum methodology to develop a Doctor Appointment application based on the Progressive Web Application (PWA). System usability testing uses the System Usability Scale (SUS) to ensure user-friendliness. The application includes doctor schedules, appointment booking, service status checking, and a visit history review. It is integrated with the Emesys system from PT Bigs Integrasi Teknologi, which serves as the case study location. The implementation of Scrum involved various stakeholders, including end-users, leading to improved team coordination and accountability through five planned sprints. The SUS testing results showed an average score of 78.58 from 30 respondents, indicating a high level of usability approaching the excellent category. This suggests that users are satisfied with the ease of use and overall application experience. However, further evaluation revealed that users may require some time to adapt to the application.